Pelatihan Dasar Penyusunan Buku Ajar Guru SMK PGRI 3 Kediri: Pelatihan Dasar Penyusunan Buku Ajar Guru SMK PGRI 3 Kediri - Siti Rochana; Alfin Febrian; Aristyawan, Rony Heri Irawan (Jurnal Pengabdian Masyarakat Nusantara, 2021)
The production of teaching books is needed as a means to support learning activities in class, especially in the development of teaching materials. At SMK PGRI 3 Kediri there is currently no training on the preparation of teaching books for teachers both basic training activities for teaching and mentoring the determination of teaching materials. Therefore, with the existence of community service activities in basic training in the preparation of teaching books at SMK PGRI 3 Kediri, it is expected to provide benefits to improve teacher skills in the development of teaching materials.